A psychological intervention for smoking cessation delivered as treatment for smokers with chronic obstructive pulmonary disease: Multiple needs of a complex group and recommendations for novel service development. (August 2015) - Yap, Su Yin; Lunn, Sarah; Pang, Elizabeth; Croft, Carla; Stern, Myra
This pilot study investigated the benefits of adjunctive psychological intervention for smokers accessing standard smoking cessation interventions. Chronic obstructive pulmonary disease (COPD) smokers attending a smoking cessation service were offered up to 12 adjunctive clinical psychology sessions. Baseline data included demographics, smoking history, and disease severity. Outcomes included attendance and quit rate. In all, 59 patients with moderate COPD were referred. Of the 20 patients who attended training sessions, 7 (35%) were relapse prevention referrals and 13 (65%) were current smokers. Of the seven relapse prevention referrals, six (86%) maintained their quit, 2 of 13 (15%) of the current smoker group maintained a 28-day quit and 3 of 13 (23%) of current smokers reduced their tobacco intake. For COPD smokers with a heavy smoking history and multiple past quit attempts, there was insufficient evidence to show that additional psychological intervention leads to higher quit rates. Significant barriers to quitting and complex medical and psychosocial needs were identified in this group, suggesting that the current 'one-size-fits-all' approach to smoking cessation may not be sufficient to meet the needs of such a complex group.